‘El Greco’s White Dollops’. Miron Białoszewski on Art - Śliwa, Anna ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
Miron Białoszewski (1922–1983) – creator of amateur, experimental theatre, poet, as well as a prose writer – was mostly considered as the inventor of new way in expressing the world in language. The spoken word was said to be his environment. There also appeared some articles and publications about the role of music in Białoszewski’s works. I thought then, what about eyesight, almost forgotten by critics? Close reading of Białoszewski’s works proves that the visual sphere can not be marginalized. Saying visual sphere, I mean not only widely understood art, but media and pop culture phenomena. The questions about visual sphere are bilateral. They refer to Białoszewski’s perception of reality, art, architecture or urbanization and, at the same time, to the way in which art and media influence his sensibility. But the most unique feature of relation between Białoszewski and art is that the visual sphere appears by the medium of language. Characters of one of Białoszewski’s prose, Rozkurz, do not look at works of art (for example paintings of El Greco) – they talk about them. The most interesting problem that appears in these conversations is the perception of the work of art.